2015
DOI: 10.1001/jama.2015.8950
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electronic Cigarette Use With Initiation of Combustible Tobacco Product Smoking in Early Adolescence

Abstract: IMPORTANCE Exposure to nicotine in electronic cigarettes (e-cigarettes) is becoming increasingly common among adolescents who report never having smoked combustible tobacco.OBJECTIVE To evaluate whether e-cigarette use among 14-year-old adolescents who have never tried combustible tobacco is associated with risk of initiating use of 3 combustible tobacco products (ie, cigarettes, cigars, and hookah). DESIGN, SETTING, AND PARTICIPANTSLongitudinal repeated assessment of a school-based cohort at baseline (fall 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
698
2
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 837 publications
(774 citation statements)
references
References 24 publications
34
698
2
15
Order By: Relevance
“…For example, a longitudinal study of 14-year-old adolescents found that e-cigarette users who did not use combustible tobacco at baseline were more likely to initiate combustible tobacco use at 1-year follow-up. 22 Similar results were observed in another longitudinal cohort study in US adolescents and young adults, in which the use of e-cigarettes at baseline was associated with progression to traditional cigarette smoking. 23 This evidence suggests the importance of public health strategies to address tobacco advertising exposure among youth.…”
Section: Discussionsupporting
confidence: 82%
“…For example, a longitudinal study of 14-year-old adolescents found that e-cigarette users who did not use combustible tobacco at baseline were more likely to initiate combustible tobacco use at 1-year follow-up. 22 Similar results were observed in another longitudinal cohort study in US adolescents and young adults, in which the use of e-cigarettes at baseline was associated with progression to traditional cigarette smoking. 23 This evidence suggests the importance of public health strategies to address tobacco advertising exposure among youth.…”
Section: Discussionsupporting
confidence: 82%
“…Other recent studies of adolescent populations in California [5,11], Connecticut [22], and Florida [23] demonstrate similarly escalating use of e-cigarettes, which has eclipsed the use of combustible cigarettes among school-aged youth. Additionally, the high prevalence of e-cigarette use in our study sample may reflect the fact that historically North Carolina adolescents have consistently used tobacco products at rates higher than the national average [17,24,25].…”
Section: Combustible Cigarette Use and Selfperceived Riskmentioning
confidence: 95%
“…Students reported their sex, race (white, African American, Asian, other), ethnicity (Hispanic, non-Hispanic), and grade (6)(7)(8)(9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“…In theory, a product that can deliver nicotine like a cigarette without the toxins found in smoke could be used instead of cigarettes would be a welcome invention 5, 6, 7. However, concerns have been raised about whether eā€cigarettes are an effective cessation aid or if they would actually reduce successful quitting by adult smokers, whether they are safe to use, and if they may be a gateway into smoking for youth 8, 9, 10. Most recently the popularity of the Juul eā€cigarette among high school and college students who have no intention of smoking has raised concerns about the risk of nicotine addiction in nonā€smokers and its longā€term health effects 11…”
Section: Introductionmentioning
confidence: 99%